PENGARUH ELEMEN-ELEMEN KEPERCAYAAN PELANGGAN TERHADAP KEPERCAYAAN ORGANISASI PADA PERUSAHAAN JASA TELEKOMUNIKASI BERBASIS GSM - Galih Chrisjatmiko (Universitas Trisakti, 2005)
The unit analysis of this research is telecommunication company based on GSM, it finds that a customer that using telephone cellular based on GSM, indicated that they are changing from post paid to prepaid. So, it indicates that customer do not want to be known about their information privacy. And then the company need to build customer's trust with the element of trust that consist of perceived risk, credibility, past experience of company, reputation of company and perception of dependability. The Objective of this research is to know how elements of trust give information a context of relationship marketing on telecommunication explanatory influence the organizational trust in desired to for company as company based on GSM. This research survey method and the sampling use purposive sampling method. Correlation and regression SPSS 11.5 is used to get an accurate answer. The result of research indicated that good implementation elements of trust can make organizational trust better. So with that, customer doesn't mind if they have to give some information for company as implementation relationship marketing.